Finland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper investigates impact of promoting labor supply through tax and benefit reform in Finland. A comprehensive reform of the tax-benefit system could support the government's objective of increasing employment. The equity-efficiency trade-off of the proposed reform scenarios improves social welfare when using Finland-specific preferences. The Finnish tax and benefit system has served the country well, having supported high income levels alongside low inequality. The model is characterized by strong institutions, high taxes and public service provision, a highly skilled labor force and a generous social safety net. The microsimulation analysis shows that, despite strong redistribution and high-income levels, Finland could improve its tax and benefit system. Even for revenue-neutral reforms, economic gains in terms of labor supply and earnings could be substantial. The reform proposals consider Finland's strong preferences for equity, while seeking to correct potential inconsistencies in how the tax burden is distributed.